Plankton do not care: Minimal effects of ocean liming on plankton growth and grazing in the Eastern Mediterranean - Claudia Traboni; Ariadna C. Nocera; Filomena Romano; Justine Courboulès; Christos Chantzaras; Iordanis Magiopoulos; Selene Varliero; Daniela Basso; Paraskevi Pitta (Limnology and Oceanography, 2025)
Increasing CO 2 emissions have led to the development of CO 2 removal strategies to counteract ocean acidification. Among these, ocean alkalinity enhancement techniques, particularly ocean liming, may represent a promising approach to restore seawater pH and boost CO 2 sequestration. Yet, the impact of liming on plankton communities remains underexplored. In the framework of a mesocosm experiment, we conducted three dilution incubations to assess natural plankton response (abundance, composition, growth, grazing, diet, and food selectivity) to liming, achieved with calcium hydroxide (Ca(OH) 2 ) additions. Experiments included two liming treatments (low concentration, and high concentration) and a control treatment without Ca(OH) 2 . The community was dominated by small‐sized plankton (bacteria, Synechococcus and pigmented picoflagellates), outnumbering larger diatoms, dinoflagellates, and ciliates. While chlorophyll a , heterotrophic bacteria, and pigmented picoflagellates remained stable across treatments, the abundance of Synechococcus and dinoflagellates increased, whereas diatoms and ciliates declined particularly under high Ca(OH) 2 . Growth and grazing rates were largely unaffected by alkalinity, except for increased growth in pigmented picoflagellates upon liming. Microzooplankton showed low ingestion of Synechococcus and pigmented picoflagellates and higher intake of diatoms, dinoflagellates, and ciliates. Food selectivity was unresponsive to liming, as the grazers selected prey based on size, regardless of Ca(OH) 2 concentrations. Increased alkalinity and pH, and the parallel effect of trophic cascades might have driven nutrient fluctuations and shaped downstream trophic interactions. Despite positive responses highlighted in this study, further research is needed to explore liming potentiality on a wider range of food‐web components and larger scales in the framework of ocean alkalinity enhancement research.

The effect of ocean alkalinity enhancement on zooplankton standing stock and community composition in the Eastern Mediterranean Sea: a mesocosm study - Ariadna C. Nocera; Claudia Traboni; Justine Courboulès; Filomena Romano; Christos Chantzaras; Iordanis Magiopoulos; Selene Varliero; Arianna Azzellino; Pietro Bazzicalupo; Piero Macchi; Guido Raos; Daniela Basso; et al. (Marine Environmental Research, 2025)

The Paleontological Heritage as a Mean for Territorial Revitalization: Innovative Communication Modalities for Pietraroja Site (Southern Italy) - Filomena Ornella Amore; Carmen Argenio; Romano Fistola; Mattia Yuri Messina; Andrea Rastelli; Ida Zingariello; Rosa Anna La Rocca (Geoheritage, 2025)

Is in-situ burning an acceptable mitigation option after a major oil spill? Impact on marine plankton - Iordanis Magiopoulos; Christos Chantzaras; Filomena Romano; Eleftheria Antoniou; Katerina Symiakaki; Rodrigo Almeda; Ioanna Kalantzi; Kyriaki Mylona; Constantine Parinos; Christina Pavloudi; Manolis Tsapakis; Giulio Zanaroli; et al. (Science of The Total Environment, 2024)

Anatomy of the uncertainty of satellite vicarious calibration using radiosondes: concepts and preliminary results for microwave radiometric observations - Domenico Cimini; Vasileios Barlakas; Fabien Carminati; Francesco De Angelis; Francesco Di Paola; Alessandro Fassò; Donatello Gallucci; Sabrina Gentile; Tim Hewison; Salvatore Larosa; Fabio Madonna; Vinia Mattioli; et al. (Bulletin of Atmospheric Science and Technology, 2024)
Calibration of satellite observations is crucial for ensuring the quality of retrieved products essential for meteorological and climate applications. Calibration is obtained and monitored through a cascade of stages, including postlaunch vicarious calibration/validation activities through comparison with independent reference measurements. Here, the vicarious calibration method using radiative transfer simulations based on reference radiosondes is considered in the framework of the calibration/validation activities for the Microwave Imager (MWI) and the Ice Cloud Imager (ICI) to be launched with the Second Generation of the EUMETSAT Polar System. This paper presents an overview of the uncertainty characterizing the vicarious calibration of MWI and ICI using radiosondes as performed within the EUMETSAT-funded VICIRS study. The uncertainty characterization is pursued following a metrological approach, providing a preliminary estimation of all the identified sources. The same approach is used to develop a rigorous method for estimating the number of comparison pairs (i.e., observations vs. simulations) needed to reach a certain level of accuracy in bias determination.

Study of the effects of pasteurization and selected microbial starters on functional traits of fermented table olives - Annamaria Tarantini; Pasquale Crupi; Francesca Anna Ramires; Leone D'Amico; Giuseppe Romano; Federica Blando; Pierpaolo Branco; Maria Lisa Clodoveo; Filomena Corbo; Angela Cardinali; Gianluca Bleve (Food Microbiology, 2024)

Temporal Variability of Planktonic Ciliates in a Coastal Oligotrophic Environment: Mixotrophy, Size Classes and Vertical Distribution - Filomena Romano; Katerina Symiakaki; Paraskevi Pitta (Frontiers in Marine Science, 2021)
The temporal variability of planktonic ciliates was studied in an extreme oligotrophic environment with special focus on trophic modes and size classes. Abundance, biomass, size classes, mixotrophy vs. heterotrophy, and species composition of planktonic ciliates were investigated focusing on temporal (samples collected on a monthly basis during 2019) and vertical (7 depth layers in the euphotic zone, from surface to 120 m) distribution at a coastal station in the oligotrophic Eastern Mediterranean. Abundance was in general very low (20 to 1150 cells L –1 ), except for September, which presented the highest abundance and biomass. Aloricate species dominated the ciliate community in all months and depths (% contribution from 77% in September to 99% in April). In general, oligotrichs presented maximum abundance at 2–10 m (except for June, July, and November: 100–120 m) whereas choreotrichs were more homogeneously distributed [and showed maxima at deep chlorophyll maximum (DCM)]. Small heterotrophs dominated the ciliate community at all depths and months, on average by 76% (they were 3 times more abundant than mixotrophs in terms of abundance and 2.5 times in terms of biomass). They were equally distributed both vertically and seasonally (and also in terms of size classes). In contrast, mixotrophs were found mainly at the surface layer to 20 m throughout the year, except for June and July (max at 100, 50 m). On average, 63% of integrated aloricate abundance was species <30 μm, of which 25% were mixotrophs. During the stratification period of May to November, the very small (<18 μm) and small (18–30 μm) mixotrophic species were distributed throughout the water column whereas the >50 μm mixotrophic species were found only above the DCM. In contrast, during the mixing period of December to May, mixotrophic ciliates were very few and were dominated by small and medium-sized species. It seems that mixotrophic and heterotrophic ciliates, on one hand, and the four size classes, on the other, are very distinct groups characterized by different distributions both vertically and seasonally. This may have important consequences for the structure and function of the microbial food web of which they are part, as well as for the carbon flow to the higher trophic levels of this oligotrophic environment in which ciliates are the main grazers.

Chemical-physical characterization of polyhydroxyalkanoates recovered by means of a simplified method from cultures of Halomonas campaniensis - Giuseppe Strazzullo; Agata Gambacorta; Filomena Monica Vella; Barbara Immirzi; Ida Romano; Valeria Calandrelli; Barbara Nicolaus; Licia Lama (World Journal of Microbiology and Biotechnology, 2008)

The familial adenomatous polyposis region exhibits many different haplotypes - Alessandro Stella; Nicoletta Resta; Angela Polizzi; Mariapina Montera; Filomena Cariola; Francesco Susca; Viviana Gismondi; Lucio Bertario; Cristiana Marchese; Romano Tenconi; Maria Grazia Tibiletti; Paola Izzo; et al. (Human Genetics, 1998)